Effect of Oblique Tendon Laceration on Core Suture Strength: A Biomechanical Evaluation. (September 2022) - Muresan, Claude; Muresan, Colin W.; Harris, Alexandria L.; Shaterian, Ashkaun; Van Royen, Kjel; Kachare, Swapnil D.; Bhandari, Laxminarayan; Palazzo, Michelle D.
Background: The effect of obliquity of tendon laceration on repair strength is not well studied. The overwhelming majority of biomechanical studies assess repair strength following a laceration that is perpendicular to the long axis of the tendon. The aim of this study was to investigate whether the angle of tendon laceration affects the core suture strength. Methods: In all, 110 fresh human cadaveric flexor tendons were cut at varying angles of 15°, 30°, 45°, and 60° and the control group at 90°. All tendons were repaired with 6-strand modified Tang technique. The repair strength was tested using a custom-made tensioning machine, and the initial static gap force and the ultimate breaking force were measured. Results: The mean gap force and 95% confidence interval (CI) for the 15°, 30°, 45°, 60°, and 90° groups were 15.2 N (11.4-19.0 N), 15.8 N (13.6-18.1 N), 15.6 N (13.1-18.4 N), 16.6 N (13.7-19.5 N), and 22.3 N (16.6-27.9 N), respectively. In the same respective order, the break force and 95% CI were 25.9 N (21.9-29.8 N), 26.5 N (23.2-29.7 N), 31.1 N (26.1-36.1 N), 35.6 N (28.2-43.1 N), and 51.8 N (62.5-41.0), respectively. The Fisher least significant difference demonstrated significant differences between the control group and all experimental groups for both gap force and break force. Conclusions: Obliquity of tendon laceration affects the core suture strength when compared with a transverse cut. Flexor tendons cut at 90° demonstrated a higher overall gap force and breaking strength that were statistically significant when compared with all obliquely cut groups. These findings should be considered when repairing and starting postoperative therapy for obliquely cut tendons.